Cost-effective building renovation at district level combining energy efficiency & renewables - Methodology assessment proposed in IEA EBC Annex 75 and a demonstration case study - Teres-Zubiaga, Jon (2020)
Building renovation plays a key role in reducing greenhouse gas emissions and achieving the climate protection goals. The district scale approach is one of the most effective approaches to accelerate this process of reducing the energy consumption in the building sector as increasing its renovation rates. In this context, the Energy in Buildings and Communities Programme of the IEA, IEA-EBC started in 2017 the project "Annex 75: Cost-Effective Building renovation at District Level Combining Energy Efficiency and Renewables" aiming to explore optimal opportunities of district renovations from a cost-benefit perspective. IEA Annex 75 is a co-operative effort of participants from 13 different countries: Austria, Belgium, China, Czech Republic, Denmark, Germany, Italy, The Netherlands, Norway, Portugal, Spain, Sweden and Switzerland. In this paper, key elements of the methodology developed in Annex 75 project are presented. This methodology aims to facilitate the identification of optimal solutions in different European countries, enabling to explore similarities and differences amongst them, with a particular focus on the balance between energy efficiency measures and renewable energy measures. After a detailed description of the developed methodology, it is also applied to a case study located in Portugal and results obtained are analysed in detail. The paper demonstrates the usefulness of the methodology for evaluating and identifying optimal solutions in renovations at district scale, as well as for successfully addressing the research questions investigated by the Annex 75 project. They also provide some insights regarding the specific case study, showing that, although district systems are not usual in the current Portuguese context, these centralised solutions in renovations at district level are cost-effective interventions that can lead to significant reductions of greenhouse gas emissions and non-renewable primary energy use. (C) 2020 Elsevier B.V. All rights reserved.